KAJIAN EKODINAMIKA HUTAN MANGROVE AKIBAT KONVERSI LAHAN DI KABUPATEN LANGKAT SUMATERA UTARA Kasus di Kecamatan Secanggang dan Kecamatan Tanjung Pura Kabupaten Langkat - , Risna Julisca Agnes Panjaitan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The existence of mangrove forests have an important role in maintaining the balance of the coastal environment, so it is important to maintain and preserve the existence of mangrove forests in the coastal areas through some effective management and utilization, as well as paying attention to the preservation of environmental functions. Therefore, this study aims to: (1) examine the ekodinamika of mangrove forests due to land conversion for culivation activities in research area